EFFECT OF INTEREST RATE AND INFLATION ON DEPOSIT AMOUNT AT BANK NAGARI PADANG MAIN BRANCH - Sari, Laynita; Wulandari, Amelia (Bina Bangsa International Journal of Business and Management, 2022)
This study aims to determine interest rates and inflation on the number of deposits at Bank Nagari Main Branch Padang. This study uses quantitative methods. The type of data used by the author is time series data. Sources of data that researchers use is secondary data. The secondary data that the author uses is in the form of financial report data for 2016-2020 from the official websites of Bank Nagari and Bank Indonesia through the websites www.banknagari.co.id and www.bi.go.id. In this study, the author uses the method of documenting a company's report. Based on the study results, interest rates have an effect on the number of deposits, inflation has no effect on the number of deposits and interest rates and inflation have a simultaneous effect on the number of deposits. These results were obtained from the Eviews8 data processing